PENDUGAAN POTENSI TEGAKAN EKALIPTUS (Eucalyptus Pellita F. Meull) MENGGUNAKAN METODE TREE SAMPLING DAN CIRCULAR PLOT - Ikhwan, Muhammad; Sadjati, Emy; Insusanty, Enny (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
The forest inventory is basically a data collection activities. This activity is relatively important, because the effect on further activities. Hence the data collected must have a high enough accuracy. A way of determining the sampling unit is considered to be simpler, easier, and faster is the tree sampl ing method. The purpose of this study was to quantify the potential large stands of eucalyptus in the Forest of eucalyptus plants in the Faculty of Forestry and calculate the relative efficiency of sample unit. The total area is 0.11 ha of eucalyptus stands. Unit examples used are circular, 4-trees sampling, sampling 5 -trees, and 6-trees sampling is done by simple random sampling method. Potential stands of eucalyptus with method 6 sample trees have an average volume stands perplot is 0.07 m3, with the volume of the stand for the entire area is 84.71 m3 with a sampling error of 36,96%. Potential stands of eucalyptus trees by the method of example 8 trees have a volume average stocking each plot is 0.04 m3, with the volume of the sta nd for the entire area is 43.22 m3 with a sampling error of 51.47%. Potential stands of eucalyptus by using 10 sample trees have an average volume stands each plot was 0.03 m3 with the volume of the stand for the entire area is 39.74 m3 with a sampling error of 53.34%. Potential stands of eucalyptus with a diameter circular sample plots of 12 m has an average volume stands each plot is 7.88 m3, with the volume of the stand for the entire area is 76.72 m3 with a sampling error of 14.43%.